(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Objective: To study start-up journey of Booz-Scooter & Torchit and to determine factors for campus startup ecosystem along with linking it to sustainable development Methodology: Case study Approach was used in this paper, wherein interview was conducted with founder of Booz-Scooter & Torchit. Major Findings: In India, many youths do possess skill sets that can be good enough for Start-up but due to lack of support or resources, they drop this idea of the start-up. This paper identifies the determinants of campus start-up ecosystem and mention the story of two start-ups from Shark Tank India Show. This case describes sustainable idea of providing e-scoters to on subscription model and Torchit is working for visually impaired community by providing them affordable navigating tools.Contribution: This paper helps in motivating upcoming start-ups and entrepreneur to adopt sustainable approach in their idea. It also links sustainable development in campus start-up ecosystem by using case study approach.